Impact of Abattoir Effluent on Soil Chemical Properties in Yola, Adamawa State, Nigeria - G. A, Abubakar; Tukur, A (International Journal of Sustainable Agricultural Research, 2014)
Despite increasing population pressure in Nigeria which resulted in increase in agricultural intensification very little attention has been paid to the soil quality. This research work was carried out to evaluate the impact of abattoir effluent on soil chemical properties in Yola, Adamawa State located on latitude 90201N and longitude 120301E. Discharging abattoir effluent to the surrounding soil had significant (P <0.05) effect on some soil chemical properties. The results revealed significant effects of abattoir effluent on soil pH, percentage organic carbon and organic matter, total nitrogen, available phosphorus, exchangeable sodium and calcium, cation exchange capacity and percentage base saturation. The results showed no significant effects on exchangeable potassium and magnesium. Highest mean values of 6.09, 0.64 Cmolkg-1 and 68.43% were observed on control samples for pH, exchangeable calcium and percentage base saturation respectively. Highest mean values of 1.70%, 2.94%, 2.81gkg-1, 5.28mgkg-1 and 3.17Cmolkg-1 were observed on samples taken from new effluent discharging area for percentage organic carbon and organic matter, total nitrogen, available phosphorus, and exchangeable sodium respectively. The highest mean value of 8.70Cmolkg-1 was observed on samples taken from the old effluent discharging area for cation exchange capacity.